Development of the Steering System for a Formula SAE Prototype - Rigo, Cristiano Shuji Shimada [UNESP]; Neto, Antonio Dos Reis De Faria [UNESP]; Grandinetti, Francisco Jose [UNESP]; Castro, Thais Santos [UNESP]; Dias, Erica Ximenes [UNESP]; Martins, Marcelo Sampaio [UNESP] (SAE International, 2024)
The SAE Formula, a national stage of the international competition, consists of a student project at universities in Brazil that seeks to encourage engineering students to apply the theoretical knowledge obtained in the classroom to practice, dealing with real problems and difficulties in order to prepare them for the job market. The SAE Formula prototype is developed with the intention of competing in the SAE national competition, where teams from various universities in Brazil meet to compete and demonstrate the projects developed during the year. Focusing on the vehicle dynamics subsystem, which can be divided into the braking, suspension, and steering systems of a prototype, the steering system includes main mechanical components such as the front axle sleeves, wheel hub, steering arm, steering column, rack, wheel, and tire. All these components work together with the suspension systems, including suspension arms, bell crank,and spring/shock absorber assembly. These components are designed and sized together to ensure the car's stability and performance in dynamic situations, allowing it to effectively transfer the power produced by the engine to the wheels. This work focused on the development of the steering system for the Unesp Racing team, founded in 2009, evaluating its dynamic behavior and the resistance of the components using 3D modeling with SpaceClaim (by Ansys) and Lotus Suspension Analysis software. The success of creating the new steering system for the prototype vehicle for the Formula SAE competition is highlighted, with the new model meeting the required parameters [4, 5].